Firearms a global history to 1700 - Chase, Kenneth Warren (Cambridge Univ. Press, 2003)
Kenneth Chase traces the history of firearms from their invention in China in the 1100s to the 1700s, when European firearms had become clearly superior. In Firearms, Chase asks why it was the Europeans who perfected firearms, not the Chinese, and answers this question by looking at how firearms were used throughout the world. Early firearms were restricted to infantry and siege warfare, limiting their use outside of Europe and Japan. Steppe and desert nomads imposed a different style of warfare on the Middle East, India, and China--a style incompatible with firearms. By the time that better firearms allowed these regions to turn the tables on the nomads, Japan's self-imposed isolation left Europe with no rival in firearms design, production, or use, with lasting consequences. After earning his doctorate from Harvard in the area of East Asian Languages and Civilizations and traveling extensively in Asia, Kenneth Chase pursued a career in the law. His interest in history endures unabated, however, and after nine years of research on firearms, he is now working on a history of international trade in the Indian Ocean region in the 1300s and 1400s.